Transportation for People with Disabilities and Older Adults During COVID-19: Lessons for Emergency Response - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The COVID-19 pandemic left many persons with disabilities and older adults without reliable transportation to access essential goods, medical care, and social engagements. Issues of social isolation for older adults were exacerbated with the emergence of COVID-19 because transportation service was reduced.TCRP Research Report 243: Transportation for People with Disabilities and Older Adults During COVID-19: Lessons for Emergency Response, from TRB's Transit Cooperative Research Program, aims to provide transportation organizations (including transit agencies, specialized transportation providers, and other local government agencies and stakeholders) with helpful information and strategies on providing service for persons with disabilities and older adults in emergency situations.Supplemental to the report is a pocket guide.
Keywords: Transportation and Infrastructure

Evidence Review of the Adverse Effects of COVID-19 Vaccination and Intramuscular Vaccine Administration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Vaccines are a public health success story, as they have prevented or lessened the effects of many infectious diseases. To address concerns around potential vaccine injuries, the Health Resources and Services Administration (HRSA) administers the Vaccine Injury Compensation Program (VICP) and the Countermeasures Injury Compensation Program (CICP), which provide compensation to those who assert that they were injured by routine vaccines or medical countermeasures, respectively. The National Academies of Sciences, Engineering, and Medicine have contributed to the scientific basis for VICP compensation decisions for decades. HRSA asked the National Academies to convene an expert committee to review the epidemiological, clinical, and biological evidence about the relationship between COVID-19 vaccines and specific adverse events, as well as intramuscular administration of vaccines and shoulder injuries. This report outlines the committee findings and conclusions.
Keywords: Health and Medicine